Metallurgy essentials - Peyret, Ricky, editor (New York, N.Y. : NY Research, 2015)
This book is an advanced text on metallurgy, redefining aspects in this vast and fast growing field of metal science. All the topics covered in this book have been written by internationally renowned experts in the field of metal science. It aims to present the most discrete researches and unexplored concepts to give a new direction to the theories in this field. This book will be beneficial for researchers, scientists, and for students who have a keen interest in the field of metallurgy.